2022
DOI: 10.7759/cureus.27948
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of COVID-19 and Pericarditis

Abstract: Coronavirus disease 2019 , caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was first identified in Wuhan, China in December 2019. Since then, the disease has spread globally, leading to the ongoing pandemic. It can cause severe respiratory illness; however, many cases of pericarditis have also been reported. This systematic review aims to recognize the clinical features of pericarditis and myopericarditis in COVID-19 patients.Google Scholar, Medline/PubMed, CINAHL, Cochrane Central, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 58 publications
(642 reference statements)
0
5
0
Order By: Relevance
“…While the exact incidence of COVID-19-related myocarditis is unknown, studies suggest that approximately 7% of COVID-19-associated deaths are linked to this condition [ 1 ]. Additionally, a systematic review by Kariyanna T et al found that COVID-19 pericarditis is more common in males, with a male-to-female ratio of two to one [ 4 ]. Myocarditis is typically caused by viral infections, such as adenovirus, enterovirus, and parvovirus [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the exact incidence of COVID-19-related myocarditis is unknown, studies suggest that approximately 7% of COVID-19-associated deaths are linked to this condition [ 1 ]. Additionally, a systematic review by Kariyanna T et al found that COVID-19 pericarditis is more common in males, with a male-to-female ratio of two to one [ 4 ]. Myocarditis is typically caused by viral infections, such as adenovirus, enterovirus, and parvovirus [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue (15%), cough (39%), and diarrhea (12%) were the next most prevalent symptoms. 15 Cardiovascular manifestations and complications following clinical recovery from SARS-CoV2 infection are unclear, and few studies have examined longterm COVID-19 patients in detail in an effort to determine the degree to which cardiovascular disturbance contributed to the development of post-recovery symptoms. 16 Our case demonstrated thrombotic complications such as coronary thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptoms reported were fever (51%), shortness of breath (51%), chest discomfort (60%), and myalgia (12%). Fatigue (15%), cough (39%), and diarrhea (12%) were the next most prevalent symptoms 15 . Cardiovascular manifestations and complications following clinical recovery from SARS‐CoV2 infection are unclear, and few studies have examined long‐term COVID‐19 patients in detail in an effort to determine the degree to which cardiovascular disturbance contributed to the development of post‐recovery symptoms 16 …”
Section: Discussionmentioning
confidence: 99%
“…She also had an acute stroke. Both pericarditis and stroke can either be due to the COVID-19 [ 14 , 15 ], or to SLE [ 16 , 17 ]. We could find only one case report of lupus cerebritis occurring three weeks after COVID-19 infection in a 29-year-old female with a past medical history of SLE, and which manifested as slow speech, psychomotor agitation, and intermittent choreiform movements in the upper part of the body [ 18 ].…”
Section: Discussionmentioning
confidence: 99%